Korelasi Kompetensi Kepribadian terhadap Penilaian Autentik Guru Bahasa Indonesia di SMA Kota Pekanbaru - Amay Lanjar Wulandari; Desi Sukenti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The aim of this research is to determine the influence of personality competence on authentic assessment in Pekanbaru City High School. This type of research is quantitative using the correlation method. The sample studied in this research was 50 respondents. The data collection technique uses a questionnaire. Data was collected from Indonesian language teachers at Pekanbaru City High School using a purposive sampling technique, namely providing a questionnaire containing statement items regarding authentic assessment and personality competence. The data that has been collected is then input in the form of a Likert scale. Data analysis uses descriptive statistics with simple linear regression analysis to find out how much influence personality competence has on authentic assessment using the SPSS version 22 application. The results of this research show that there is a positive influence between personality competence and authentic assessment of Indonesian language teachers. Teachers who have a good and wise personality can professionally carry out assessments of their students at school without discriminating against religion, culture and ethnicity. So it can be concluded in this research that teacher personality competence influences the authentic assessment of Indonesian language teachers.